Lipidomics and Redox Lipidomics Indicate Early Stage Alcohol‐Induced Liver Damage. Issue 3 (23rd November 2021) - Koelmel, Jeremy P.; Tan, Wan Y.; Li, Yang; Bowden, John A.; Ahmadireskety, Atiye; Patt, Andrew C.; Orlicky, David J.; Mathé, Ewy; Kroeger, Nicholas M.; Thompson, David C.; Cochran, Jason A.; Golla, Jaya Prakash; et al.
Abstract : Alcoholic fatty liver disease (AFLD) is characterized by lipid accumulation and inflammation and can progress to cirrhosis and cancer in the liver. AFLD diagnosis currently relies on histological analysis of liver biopsies. Early detection permits interventions that would prevent progression to cirrhosis or later stages of the disease. Herein, we have conducted the first comprehensive time‐course study of lipids using novel state‐of‐the art lipidomics methods in plasma and liver in the early stages of a mouse model of AFLD, i.e., Lieber‐DeCarli diet model. In ethanol‐treated mice, changes in liver tissue included up‐regulation of triglycerides (TGs) and oxidized TGs and down‐regulation of phosphatidylcholine, lysophosphatidylcholine, and 20‐22‐carbon‐containing lipid‐mediator precursors. An increase in oxidized TGs preceded histological signs of early AFLD, i.e., steatosis, with these changes observed in both the liver and plasma. The major lipid classes dysregulated by ethanol play important roles in hepatic inflammation, steatosis, and oxidative damage. Conclusion: Alcohol consumption alters the liver lipidome before overt histological markers of early AFLD. This introduces the exciting possibility that specific lipids may serve as earlier biomarkers of AFLD than those currently being used. Abstract : image